The Influence of Corporate Governance on Tax Management in Consumer Goods Industry Sector Companies Listed on The Indonesian Stock Exchange In 2017-2019 - Jamali, Hisnol (Economics and Business Journal (ECBIS), 2023)
This research aims to determine whether public ownership, board of directors compensation and audit committee have an effect on tax management in basic consumer goods industrial companies listed on the Indonesian Stock Exchange. Secondary data was obtained based on purposive sampling of financial reports. The population was conducted on basic consumer goods industrial companies listed on the IDX with a number of 54 companies, while the samples were selected with purposive sampling method obtained a total of 12 companies or 36 samples for the period 2017-2019. But the 36 samples processed the result is abnormal distribution, so the researcher increase the observation period on the IDX in 2015.2020. Data analysis method used is multiple linear regression. The results of this research indicated that the public ownership, board of directors compensation and audit committee no have significant effect on the tax management.